Establishing a critical care network in Asia to improve care for critically ill patients in low- and middle-income countries - Beane, Abi; Dondorp, Arjen M.; Taqi, Arshad; Ahsan, A. S. M. Areef; Kumar, Bharath; Vijayaraghavan, Tirupakuzhi; Permpikul, Chairrat; Pell, Christopher; Mat Nor, Mohd Basri; Gandy, David; Priyadarshani, Dilanthi; Aryal, Diptesh; et al. (BioMed Central Ltd, 2020)
When undertaking quality improvement (QI) initiatives, one of the greatest burdens is repeated data collection. Intensive care registries, such as those commonly used in high-income countries (HICs), have enabled systematic capture of routine information needed to measure intensive care unit (ICU) performance. Once considered unfeasible in resource-limited settings, newer cloud-based platforms are gaining increasing traction. Collaborative surveillance platforms, such as NICS-MORU and PRICE, which have mobile and desktop applications, have established methods for daily capture of individual patient-level information and have shown that—even in resource-limited settings—the systematic evaluation of patient care throughout the hospital journey is feasible at scale using coalesced minimal data sets.